Integrating Digital Literacy in the Ecological Environment of Child Development - Haryani, Yunita; Rahayu, Nenden Sri (Jurnal Ilmiah Mandala Education (JIME), 2025)
Today, digital technology is developing very rapidly and has an impact on various aspects of life, both adults and children. Therefore, digital literacy is a skill that needs to be instilled from an early age. This research aims to examine in depth how digital literacy can be integrated in the context of the ecological environment of child development based on Bronfenbrenner's ecological theory. The method used is library research with a descriptive qualitative approach. Data were obtained from various sources of scientific literature, including books, journals, academic articles and educational policy documents. The results showed that digital literacy is not only influenced by individual factors, but also involves the entire system in the child's environment, ranging from microsystems to macrosystems and paying attention to the dynamics of the chronosystem. Each layer of the environment has an important role in shaping children's healthy, critical and responsible digital understanding, attitudes and skills.